Peran Pendidikan Islam dalam Menanggulangi Perilaku Menyimpang Pelajar di Era Digital - Febi Syafitri; Naylah Agastiya Rinaldi; Gusmaneli Gusmaneli (CV. ITTC INDONESIA, 2025)
Deviant behavior of students in the digital era is increasing, along with the development of information and communication technology. Gadget addiction, excessive use of social media, cyberbullying, online gambling, and moral degradation are phenomena that are often found among students. Factors such as unpreparedness to filter information, lack of parental and school supervision, and the influence of the social environment worsen this condition. Character education based on religious values, especially in Islamic education, can be a solution to shape students' digital morals and ethics. Islamic educational institutions need to play an active role in character building and supervising the use of technology. With the right approach, it is hoped that students can use technology wisely and avoid deviant behavior.